2017
DOI: 10.4049/jimmunol.1600979
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Killed Blood-Stage Vaccine-Induced Immunity Suppresses the Development of Malaria Parasites in Mosquitoes

Abstract: As a malaria transmission-blocking vaccine alone does not confer a direct benefit to the recipient, it is necessary to develop a vaccine that not only blocks malaria transmission but also protects vaccinated individuals. In this study we observed that a whole-killed blood-stage vaccine (WKV) not only conferred protection against the blood-stage challenge but also markedly inhibited the transmission of different strains of the malaria parasite. Although the parasitemia is much lower in WKV-immunized mice challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
(39 reference statements)
0
8
1
Order By: Relevance
“…The pRBC lysate preparation and vaccine immunization schedule were carried out as previously described . Briefly, when the parasitemia of P yoelii NSM‐infected mice reached 30%‐40%, blood was collected into heparinized tubes and washed with sterile PBS (1000 g for 10 minutes).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pRBC lysate preparation and vaccine immunization schedule were carried out as previously described . Briefly, when the parasitemia of P yoelii NSM‐infected mice reached 30%‐40%, blood was collected into heparinized tubes and washed with sterile PBS (1000 g for 10 minutes).…”
Section: Methodsmentioning
confidence: 99%
“…The pRBC lysate preparation and vaccine immunization schedule were carried out as previously described. 9,13 Briefly, when the parasitemia of P yoelii NSM-infected mice reached 30%-40%, blood was collected into heparinized tubes and washed with sterile PBS (1000 g for 10 minutes). Total RBC counts and parasitemias were determined, and the parasites were adjusted to the desired concentrations with the sterile PBS.…”
Section: Immunization and Challengementioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, wholeparasite vaccines against the pre-erythrocytic stage, such as chemically and genetically attenuated sporozoites, have been shown to induce cross-stage protection against the blood stage (Nahrendorf et al, 2015b;Sack et al, 2015). Although the protection induced by chemically attenuated blood-stage P. yoelii parasites was stage specific as immunized mice were not protected against intravenous or mosquito bite sporozoite challenges (Raja et al, 2016), our study showed that the WKV not only conferred the cross-stage immunity against sporozoite challenge but also blocked parasite development in mosquitoes (Figure 2; Lu et al, 2017;Zhu et al, 2017). Therefore, the WKV not only prevents malarial infection and reduces mortality and morbidity among malaria patients but also blocks malaria transmission.…”
Section: Promising Malaria Vaccine: Whole-parasite Blood-stage Vaccinementioning
confidence: 71%
“…Effector CD4 ϩ T cells are also important sources of cytokines that activate macrophages and other immune effector cells. Although the role of CD4 ϩ T cells in the induction of antibodies against asexualstage P. falciparum parasites has been studied extensively (56), their role in inducing gametocyte-specific antibodies is not well established (57)(58)(59). In general, antibody responses against gametocyte antigens tend to be lower than anti-asexual-antigen responses, but the intensity and breadth of the response increases over the season, suggesting boosting during reexposure (60).…”
mentioning
confidence: 99%